The Character and Legal Effect of the Decisions of the Constitutionals Courts (Comparative Overview of the European Models of Control of Constitutionality) - Jelena Trajkovska Hristovska (Law Review ,,Iustinianus Primus", 2022)
The establishment of the system of control of the constitutionality of acts by the constitutional court consequently imposes one very important issue - the issue of the legal effect of its decisions. The efficiency of the system of control of constitutionality depends directly on the effect of the decisions that the constitutional courts make. The fact that this issue is materia constitutionis in comparative constitutional law and issue that is regulated by the laws (acts) for the constitutional courts, is the most significant evidence of its importance. The paper will present a comparative overview of normative frame regarding the character and legal effect of the decisions of the European constitutional courts. The paper will analyze the decisions of the constitutional courts of Germany, the Republic of Italy, as well as the character and legal effect of the decisions of the Constitutional Court of Republic of Slovenia. Тhe paper will analyzе the interpretive decisions of the constitutional courts, whose adoption deviates from the classical understanding of the role of the constitutional court as a negative legislator. Therefore they are assessed as a possible mechanism for the court to operate outside the established functions and competencies
Keywords: Constitutional court, control of constitutionality, interpretative decisions, cassation decisions, manipulative decisions